2022
DOI: 10.3389/feduc.2022.1062922
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cognitive combat readiness: Gamers’ Behaviours concentrating on convergent learning style, tacit-latent, and kinetic-active knowledge acquisitions

Abstract: This study investigates gamers’ learning styles and knowledge acquisition behavioural patterns. It argues that gamers usually have different characteristics transforming themselves to gain distinctive competencies. In other words, this study mitigates gamers’ mechanistically distinctive attitudes and behaviours, enhancing their cognitive combat readiness, that they are on convergent learning style, tacit-latent, and kinetic-active knowledge acquisitions. Methodologically, it uses a field-experimental design us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 95 publications
(205 reference statements)
0
4
1
Order By: Relevance
“…The results of this analysis indicate that MR, as a facilitator and transmitter tool in the learning process, accelerates and clarifies cognitive absorption and learning achievement. Therefore, the dichotomous distinction of high-low MR role types affects students' convenience in adding knowledge to their cognitive abilities [27,49,52]. However, this research did not find that students with high cognitive and psychological endowment and high MR showed cognitive absorption and learning achievement that were in contrast to the others.…”
Section: Discussion and Findingscontrasting
confidence: 56%
See 4 more Smart Citations
“…The results of this analysis indicate that MR, as a facilitator and transmitter tool in the learning process, accelerates and clarifies cognitive absorption and learning achievement. Therefore, the dichotomous distinction of high-low MR role types affects students' convenience in adding knowledge to their cognitive abilities [27,49,52]. However, this research did not find that students with high cognitive and psychological endowment and high MR showed cognitive absorption and learning achievement that were in contrast to the others.…”
Section: Discussion and Findingscontrasting
confidence: 56%
“…On the other hand, individuals with attached entities and insecure perspectives trigger self-validation goals, decreasing their learning performance. Therefore, this study posits Baum and Owen [47], Sher-Censor et al [16], Sriwidharmanely et al [48], and Sumiyana et al [49], who revealed that students with high-learning abilities could easily understand various levels of material compared to others. Moreover, they continue to make learning achievements, even utilising them in opportunistic conditions.…”
Section: Student Learning Attachment and Performancementioning
confidence: 77%
See 3 more Smart Citations